(untitled) (Journal of Informatics Education and Research, 2026)
Oral traditions are vital for preserving cultural identity and collective memory, but they are becoming less significant for younger generations in digitally influenced societies. In India, the passing down of folklore has been interrupted by urban development, structured education systems, and the influence of worldwide digital media platforms. This study explores immersive media, especially Virtual Reality (VR) and interactive digital storytelling, as means to enhance folklore participation and safeguard intangible cultural heritage. Utilizing participatory culture, narrative transportation, and cultural memory theory, the research employs a qualitative case study method to examine how groundbreaking international immersive storytelling initiatives have effectively set global best practices, followed by an exploration of Indian projects that modify immersive media to fit local cultural contexts. These efforts utilize immersive or interactive media to reimagine folklore and cultural stories. The results indicate that immersive storytelling boosts emotional involvement, narrative connection, and cultural interest while also elevating ethical issues concerning authenticity, representation, and ownership of narratives. The results indicate that immersive storytelling increases emotional involvement, narrative connection, and cultural curiosity in young people, while also bringing up ethical issues related to authenticity, representation, and narrative ownership. The research adds to media and communication studies by framing immersive storytelling as a culturally important medium that connects heritage with technological advancement. The article also contends that immersive media, when created responsibly and in collaboration, can serve as a link between heritage and technological advancement.